Massive Preplacental Hematoma Associated with an Uneventful Pregnancy Outcome: A Case Report - Vidushi Sharma; Sravan K. Reddy; Neha Khatoon; Abhishikth Verapala (Asian Journal of Medical Radiological Research, 2022)
We report an uncommon case of massive pre-placental hematoma occurring in a 26-year-old woman who came for a regular antenatal checkup around 21 weeks of gestation. Ultrasonography showed a haematoma in the preplacental region of posteriorly located placenta, measuring 3.7 cm in largest diameter. Pre-placental haematoma continued to grow, measuring 8.0 cm at 30 weeks, and 11 cm at 36 weeks. At 37 weeks, the patient presented with rupture of membranes and an emergency caesarean section was performed. Both mother and child recovered well. The current literature on such haematomas is reviewed.